Widespread white matter degeneration preceding the onset of dementia - Maier-Hein, Klaus H.; Westin, Carl-Fredrik; Shenton, Martha E.; Weiner, Michael W.; Raj, Ashish; Thomann, Philipp; Kikinis, Ron; Stieltjes, Bram; Pasternak, Ofer (Alzheimer's and dementia, 2015)
Abstract Background Brain atrophy in subjects with mild cognitive impairment (MCI) introduces partial volume effects, limiting the sensitivity of diffusion tensor imaging to white matter microstructural degeneration. Appropriate correction isolates microstructural effects in MCI that might be precursors of Alzheimer's disease (AD). Methods Forty-eight participants (18 MCI, 15 AD, and 15 healthy controls) had magnetic resonance imaging scans and clinical evaluations at baseline and follow-up after 36 months. Ten MCI subjects were diagnosed with AD at follow-up and eight remained MCI. Free-water (FW) corrected measures on the white matter skeleton were compared between groups. Results FW corrected radial diffusivity, but not uncorrected radial diffusivity, was increased across the brain of the converted group compared with the nonconverted group (P < .05). The extent of increases was similar to that found comparing AD with controls. Conclusion Partial volume elimination reveals microstructural alterations preceding dementia. These alterations may prove to be an effective and feasible early biomarker of AD.